ANALISIS KOMPONEN LANGUAGE KERANGKA KERJA ELPSA TERHADAP KEMAMPUAN MENGAJUKAN MASALAH MATEMATIKA SISWA SMP DITINJAU DARI GAYA BERPIKIR KOGNITIF - Indriani, Kanti Warih Ade; Lutfianto, Fauzi Galih (Universitas Pendidikan Mandalika (UNDIKMA), 2018)
From the experience and observation of the author, during this learning of Mathematics generally only solve the problem alone, without familiarize the students to compile their own questions. So that students are less able to use their own language in solving the given problem. Language factor is less calculated as a possible one of the causal factors. ELPSA is a design/learning framework consisting of 5 component sequences, one of which is language. In learning ELPSA students are accustomed to asking productive and effective questions. This study aims to analyze the students' language skills in ELPSA learning design on the ability to issue Mathematical problems in terms of the cognitive thinking style. This study is a descriptive qualitative research. The subject of this research was conducted in class VIII SMP 1 Maluk. Its divided into two groups. With one group is given conventional learning and one group get learning using ELPSA design. The instrument used is Matching Familiar Figure Test (MFFT) to find out the type of cognitive style of each student and the Matter of Matter Problem Matter. Based on research that has been done, obtained results group of students reflective dominant than Impulsive students. In the student's ability to pose mathematical problems, Reflective student groups are better than Impulsive. While on the average score on the ability to solve Mathematics problems, Learning using ELPSA design is higher than learning without using ELPSA. That is, ELPSA learning design can help students develop language skills especially in raising math problems.